PENINGKATAN KESADARAN PENGGUNAAN ALAT KESELAMATAN PELAYARAN BAGI NELAYAN DI KABUPATEN MUSI BANYUASIN - Driaskoro Budi Sidharta; Sri Kelana; Slamet Prasetyo Sutrisno (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2021)
One of the important roles in using shipping safety equipment is an effort to prevent or minimize accidents for fishermen. The low awareness and the price of safety equipment that is considered quite expensive make fishermen in Musi Banyuasin regency less caring about the importance of shipping safety equipment. The program was carried out to share knowledge about safety voyage for fisherman Musi Banyuasin regency. It was held to improve skill, attitude, and awareness of fisherman in Musi Banyuasin regency regarding to the importance of safety, life saving technique in accident case. This program was conducted by lectures and discussion method between speaker and participants focusing in safety voyage. The results showed that the participant’s awareness of safety voyage importance and understanding of life saving technique have increased. The lifejackets were given to help participants to comply the life saving requirement during fishing.